Founder control, ownership structure and firm value: Evidence from entrepreneurial listed firms in China - Lijun Xia (China Journal of Accounting Research, 2008)
In emerging markets, the deviation between the ultimate controlling shareholders' voting rights and their cash flow rights (hereafter 'DVC') in the listed firms is quite prevalent. DVC could be introduced due to the ultimate controlling shareholders' opportunistic incentives, as well as by their incentives to improve firm efficiency. This study uses 229 listed firms ultimately controlled by individuals or families (hereafter 'entrepreneurial firms') for 2004 in China, to investigate the effect of DVC on firm value and to determine whether it is different between founder and non-founder controlled firms. We find that DVC has a positive effect on firm value for founder controlled firms. This result implies that investors believe that their interests are better protected by founder controlled firms than by non-founder controlled firms.
Keywords: G34; G32; 650; Founder Control; Ownership Structure; Firm Value; China; Tunneling